Tara, Irland: Landschaftsarchäologische Forschungen am Königssitz von Tara - Beusing, Ruth; Rassmann, Knut (e-Forschungsberichte des DAI, 2023)
The Hill of Tara (Co. Meath, Ireland) holds a fascination as one of the preeminent icons of Irish culture and identity. Its 5,000 years of history seem to be preserved eternally within the burials, embankments and enclosures visible in the landscape, well known to every Irishman from myths and history. But underneath its topsoil more monuments are currently being discovered by modern nondestructive survey methods in a joint programme of the Romano- Germanic Commission, the Discovery Programme Dublin and the National University of Ireland Galway. More than 50 ha of the Tara area have been surveyed geomagnetically and hundreds of new archaeological structures have been detected in the area. The analysis of the data will bring new insights into the vivid history of the site, and comparison with further sites in the surrounding landscape will highlight the tight network of the sacred site.